Perioperative Transfusion Associated With Increased Morbidity and Mortality in Geriatric Patients Undergoing Hip Fracture Surgery. (13th May 2021) - Gupta, Piyush; Kang, Kevin K.; Pasternack, Jordan B.; Klein, Elliot; Feierman, Dennis E.
Introduction: Both conservative and liberal transfusion thresholds, in regard to hematocrit and hemoglobin levels, have been widely studied with varying outcomes. The aim of this study was to evaluate if transfusion administered peri- (anytime during the admission), pre-, intra-, or postoperatively an its association with morbidity and mortality in the geriatric population undergoing hip surgery. Methods: This study was an institutional review board approved retrospective analysis of data collected from 841 patients at a single urban institution who underwent surgical repairs for hip fractures from 2008 to 2010. Results: Our analysis included data from 841 surgical patients. Mean patient age was 83, 74% were female, 48% received spinal anesthesia while 52% underwent general anesthesia. Out of 841 patients, 425 were transfused during the perioperative period. Most transfusions occurred postoperatively. Perioperative, intraoperative and postoperative transfusion was associated with an increase in post-operative AKI. Intraoperative blood transfusion was associated with an increase in morbidity (11.6% increased to 22.2%) by 1.9 fold, AKI (3.9% increased to 11.1%) by 2.8 fold, as well as an increase in mortality (5.2 increased to 15.6%) within 60 days by 3 fold. Conclusions: This may suggest that patients transfused prior to surgery, despite having met a specific trigger hemoglobin level earlier, may have been treated before deteriorating to a point that would cause future systemic implications.